2013
DOI: 10.1111/eci.12103
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for anti‐angiogenic therapy in abdominal aortic aneurysms

Abstract: Objective Abdominal aortic aneurysm (AAA) is a condition that mainly affects elderly men. At present, there is no effective medical therapy that can retard aneurysm growth or prevent aneurysm rupture. There is evidence that angiogenesis within the wall of an aortic aneurysm may play key roles in aneurysm progression as well as rupture. The use of anti-angiogenic therapy as potential medical therapy in AAA is a promising strategy but has never been studied in detail.Design This paper discusses the basic mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Angiogenesis is thought to contribute to destructive processes within the AAA wall and plays a key role in aortic aneurysm development and rupture [7]. Therefore, various anti-angiogenic agents have been studied in animal models for potential treatment of AAA [30], [49], [50]. Maruyama et al reported that down-regulation of VEGFR-3 and subsequent inhibition of lymphangiogenesis delayed diabetic wound healing in a mouse model [51].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is thought to contribute to destructive processes within the AAA wall and plays a key role in aortic aneurysm development and rupture [7]. Therefore, various anti-angiogenic agents have been studied in animal models for potential treatment of AAA [30], [49], [50]. Maruyama et al reported that down-regulation of VEGFR-3 and subsequent inhibition of lymphangiogenesis delayed diabetic wound healing in a mouse model [51].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis has been proven to be a pathological hallmark of AAA in both human and animal models, and it plays an important role in the development and progression of AAA (1215). Higher levels of neovascularization are detected at the rupture edge in aortic aneurysm, suggesting that imaging of molecules and processes involved in angiogenesis can potentially depict high-risk aneurysms (16).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis in the adventitia and media, along with CD34+ cell infiltration, is a general observation in human AAA, depending on intima/media thickness and the grade of inflammation. This is currently under investigation with the treatment of angiogenesis inhibitors [28]. …”
Section: Discussionmentioning
confidence: 99%